2012
DOI: 10.4236/pp.2012.32034
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Screening of New 5-Substituted-1,3,4-oxadiazole-2-thioglycosides as Potent Anticancer Agents

Abstract: A series of newly 1,3,4-oxadiazole-2-thioglycoside derivatives were synthesized. The key step of this protocol is the coupling between 5-herteroaryl-1,3,4-oxadiazole-2-thione and activated sugars (cyclic or acyclic sugar analogues) in the presence of basic medium. Among of the synthesized compounds, compounds 7, 10, 11 and 13 were screened for them in vitro anticancer activity against four human cancer cells. MCF-7 (Breast), HEPG2 (Liver), HCT116 (Colon) and HEP2 (Larynx) carcinoma cell lines with IC50 values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…There are several methods described in literature of ester 1 conversion to hydrazide 3 in 80-90% yields by treating it with hydrazine hydrate in methanol [52] or ethanol. [31,45,[53][54][55] Mamdouh et al [45,47] showed that hydrazide 3 can be reacted with carbon disulfide in the presence of ethanolic potassium hydroxide, followed by acidification with dilute hydrochloric acid to give the 1,3,4-oxadiazoles derivative 4. In this study, a similar path has been chosen with minor changes.…”
Section: Chemistrymentioning
confidence: 99%
“…There are several methods described in literature of ester 1 conversion to hydrazide 3 in 80-90% yields by treating it with hydrazine hydrate in methanol [52] or ethanol. [31,45,[53][54][55] Mamdouh et al [45,47] showed that hydrazide 3 can be reacted with carbon disulfide in the presence of ethanolic potassium hydroxide, followed by acidification with dilute hydrochloric acid to give the 1,3,4-oxadiazoles derivative 4. In this study, a similar path has been chosen with minor changes.…”
Section: Chemistrymentioning
confidence: 99%
“…For example, capecitabine [14], N-nucleoside and C-nucleoside, are applied in the treatment of metastatic breast cancer and hairy cell leukemia, respectively. Recently, a number of S-glycosides, a new non classical class of nucleosides, have been proved to be potential anticancer agents against many cell lines [17][18][19][20][21][22]. Elgemeie et al described the synthesis of series of heterocyclic thioglycosides, pyridine [33], benzisoquinoline [16] and pyrimidinthione [34] thioglycosides and revealed their potential antitumor activities.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36][37].Khodair et al described the synthesis of a series of heterocyclic S-glycosides, thiohydantoins[47][48][49][50][51][52][53][54][55][56][57][58][59], rhodanines[60], thioquinazolines[61,62], thiopyridines[63][64][65], and thiopyrimidine[66] S-glycosides and revealed their potential antitumor activities.…”
mentioning
confidence: 99%